Mutational alterations in the QRDR regions associated with fluoroquinolone resistance in Pseudomonas aeruginosa of clinical origin from Savar, Dhaka - Md. Shamsul Arefin; Meftahul Jannat Mitu; Shomaia Yasmin Mitu; Azmery Nurjahan; Mir Mobin; Shamsun Nahar; Hasnain Anjum; M. Hasibur Rahman (PLoS ONE, 2025)
Bacterial DNA gyrase and topoisomerase IV are the major targets of quinolone antibiotic, and mutational alterations in quinolone resistance determining regions (QRDR) serve as major mechanism of resistance in most bacterial species, including P. aeruginosa. The present investigation was aimed to study the molecular mechanism of fluoroquinolone resistance among clinical P. aeruginosa isolated from Dhaka, Bangladesh, including alterations in target sites of the antimicrobial action. Laboratory collection of 53 P. aeruginosa were subjected to conventional cultural and biochemical characterization, followed by molecular identification using 16S rDNA sequencing. Susceptibility to ciprofloxacin and levofloxacin was tested by disc diffusion method followed by MIC assay. Resistant isolates were analyzed for mutation in their QRDR regions of gyrA and parC, and subjected to PCR detection of plasmid mediated quinolone resistance (PMQR) genes qnrA, qnrS and qnrB. Among the isolates, 28% were found to be resistant to both fluoroquinolones tested. All of the fluoroquinolone resistant isolates carried a single mutation in gyrA (Thr-83-Ile), while 20% carried a single parC mutation (Ser-87-Leu). Higher level of MIC was observed in isolates carrying alterations at both sites. None of the isolates harbored any PMQR genes investigated, suggesting that chromosomal mutations in QRDR regions to be the major contributing factor for quinolone resistance in P. aeruginosa under investigation.